Human Security In The Niger Delta: Exploring The Interplay Of Resource Governance, Community Structure And Conflicts - Ajala, Olayinka (Journal of Sustainable Development Law and Policy, 2025)
Prior to August 2009, the Niger Delta region of Nigeria witnessed widespread violent conflicts between the government, multinational oil corporations (MNCs) and militant groups. This conflict was widely attributed to deplorable human security, which deprived the indigenes of the region access to their sources of livelihoods due to pollution, by MNCs. In 2009, the government granted amnesty to thousands of ‘repentant militants’ and this programme has achieved mixed results. This article will explore the impact of human security on the outbreak of violence in the Niger Delta and the impact of the Amnesty Programme in addressing issues relating to human security. The article concludes that bottom-up community-driven initiatives offer the best approach to address human security issues in the Niger Delta. The article is based on an ethnographic research carried out in 2013 in three states in the region (Bayelsa, Delta and Rivers states).